A new therapeutic protocol for the treatment of keloid scars: a retrospective study. (2nd March 2021) - Boccara, David; Serror, Kevin; Chatelain, Sarah; Chaouat, Marc; Mimoun, Maurice; Azoulay, Laura
Abstract : Objective: There are few means to treat large keloid scars, as exeresis—even if partial—impedes direct closure without tension in the absence of a flap or a skin graft. This study evaluates the efficacy, indications for use and limitations of a new therapeutic protocol, combining an extralesional keloid excision left to heal by secondary intention with a paraffin dressing and glucocorticoid ointment, followed by monthly intrascar injections of corticosteroids upon full re-epithelialisation. Method: A retrospective study of patients treated for keloid scars by using the new therapeutic protocol. Scars were categorised as either healed or recurring. Their recurrence was scored according to the changes in functional signs and the scar volume. Results: A total of 36 scars were studied. The mean follow-up was 14.1 months. Healing occurred in a mean of 6.8 weeks. The mean surface area was 21.6cm 2 . Healing rate was 30.5%. Scar volume was improved in 60% of recurrent cases and functional signs in 56%. Based on adherence with the corticotherapy, two patient groups could be discerned. For patients in the 'adherent' group, the healing rate was 40%, and scar volume was improved in 75% of recurrent cases and the functional signs in 83% of cases. Conclusions: The healing rate in this study was close to that reported in the literature. Excision-healing by secondary intention could therefore be offered to patients for whom adherence is uncertain. The protocol in this study offers a straightforward, fast, accessible solution that does not appear to entail any risk of additional keloids. It could potentially offer a treatment option in case of failure of other treatments, large keloid scars or scalp keloids.